The Effect of Entrepreneurial Motivation And Self-Efficacy On The Performance of Umkm Types of Culinary Micro-Businesses Through Entrepreneurial Education In Serang City - Susi Mulyati; Ahmad Mukhlis; Khaeruman (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the influence of entrepreneurial motivation and self-efficacy on the performance of culinary micro-enterprises in Serang City, both directly and indirectly through entrepreneurial education as an intervening variable. The research method used is a quantitative approach with a survey technique using a Likert scale questionnaire. The research sample was determined through a purposive sampling method of culinary micro-SMEs. Data analysis was conducted using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. The results of the study indicate that entrepreneurial motivation and self-efficacy have a positive and significant effect on MSME performance. Furthermore, entrepreneurial motivation and self-efficacy also have a positive and significant effect on entrepreneurial education. Entrepreneurial education has been shown to have a positive and significant effect on MSME performance and acts as an intervening variable in the relationship between entrepreneurial motivation and self-efficacy on MSME performance. These findings indicate that increasing motivation, self-confidence, and the quality of entrepreneurial education simultaneously can strengthen the performance of micro-enterprises in the culinary sector. This study provides theoretical contributions in the development of entrepreneurial behavior models and practical implications for local governments and stakeholders in designing more effective, targeted, and sustainable MSME empowerment programs to increase local economic competitiveness.